Structuralism and its Chinese ancestors: Traditional Chinese perception theories and the concept of structure (li) - S. Rošker, Jana (Anali PAZU HD, 2022)
Before the impact of Western thought which became increasingly strong after the 18th century, Chinese epistemologies were, in essence, structural or relational systems of comprehension. In such a view, the objet of perception are relations, forming a relative fixed structure. In China, the structural approach to comprehension had already been elaborated in ancient times. It has been developed as an abstract model conditioned by the supposition of an existing compatibility between the structures of the external world and those of the human mind. In such view, structural compatibility of the subject and the object of comprehension was the basic precondition of human perception. The structural link between human consciousness on the one, and the external reality on the other side, has been expressed by the term li 理, which was seen as a basic concept of dynamic and all-encompassing structure.
Keywords: Structure; the concept li; Chinese philosophy; structural compatibility; Chinese perception theories